2017
DOI: 10.1115/1.4035616
|View full text |Cite
|
Sign up to set email alerts
|

Strain Rate and Stress-State Dependence of Gray Cast Iron

Abstract: An investigation of the mechanical strain rate, inelastic behavior, and microstructural evolution under deformation for an as-cast pearlitic gray cast iron (GCI) is presented. A complex network of graphite, pearlite, steadite, and particle inclusions was stereologically quantified using standard techniques to identify the potential constituents that define the structure–property relationships, with the primary focus being strain rate sensitivity (SRS) of the stress–strain behavior. Volume fractions for pearlit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The ASTM Standard E562-02 [23] was used for statistically estimating the volume fraction of the identifiable phases. The volume fraction is determined assuming that the area fraction is equivalent to the volume fraction for the randomly distributed particles [23,24]. The volume fraction of the phases of interest and the observed porosities in the as-cast component are summarized in Table 3.…”
Section: Microstructurementioning
confidence: 99%
“…The ASTM Standard E562-02 [23] was used for statistically estimating the volume fraction of the identifiable phases. The volume fraction is determined assuming that the area fraction is equivalent to the volume fraction for the randomly distributed particles [23,24]. The volume fraction of the phases of interest and the observed porosities in the as-cast component are summarized in Table 3.…”
Section: Microstructurementioning
confidence: 99%
“…Gray cast iron shows brittle behavior in tension and a ductile behavior during compression. 36 So, this model is based on a yield function dependent on the maximum principal stress during tension loadings, and the Von Mises yield criterion during compression. The hardening of gray cast iron is independent of tension and compression.…”
Section: Materials Modelmentioning
confidence: 99%
“…However, no quantification of the results in dependence on the microstructure was carried out [6]. Brauer et al observed that the strength properties of grey cast iron increase by about 15–20% when the strain rate is raised from 10 −3 to 10 3 s −1 [7]. The data shown so far demonstrates that the toughness in CI testing deviates significantly from toughness properties in the actual loading situation of the component.…”
Section: Introductionmentioning
confidence: 99%